Internal Quality Control of PCR-based Genotyping Methods in Research Studies and Patient Diagnostics - Bladbjerg, Else-Marie; Gram, Jørgen; Jespersen, Jørgen; de Maat, Moniek P. M. (Thrombosis and Haemostasis, 2002)
Genetic analyses are increasingly integrated in the clinical laboratory, and internal quality control programmes are needed. We have focused on quality control aspects of selected polymorphism analyses used in thrombosis research. DNA was isolated from EDTA-blood (n = 500) by ammonium acetate precipitation and analysed for 18 polymorphisms by polymerase chain reaction (PCR), i. e. restriction fragment length polymorphisms, allele specific amplification, or amplification of insertion/deletion fragments. We evaluated the following aspects in the analytical procedures: sample handling and DNA-isolation (pre-analytical factors), DNA-amplification, digestion with restriction enzymes, electrophoresis (analytical factors), result reading and entry into a database (post-analytical factors). Furthermore, we evaluated a procedure for result confirmation. Isolated DNA was of good quality (42 µ.g/ml blood, A260/A280 ratio >1.75, negative DNAsis tests), and the reagent blank was contaminated in <1% of the results. Occasionally, results were re-analysed because of positive reagent blanks (<1%) or because of problems with the controls (< 5%). On confirmation, we observed 4 genotyping discrepancies. Control of data handling revealed 0.1% reading mistakes and 0.5% entry mistakes. Based on our experiences we propose an internal quality control programme for widely used PCR-based haemostasis polymorphism analyses.
Keywords: Quality control; DNA-analyses; PCR; polymorphism; haemostasis